Electrocatalytic reduction system for preparing ethylene by electrochemically reducing carbon dioxide and application of electrocatalytic reduction system
By adding sucrose as an electrolyte additive to the Cu-based catalyst and combining with the copper nanoparticle network structure, the Faraday efficiency of carbon dioxide reduction ethylene is significantly improved, the problem of insufficient activity of Cu-based catalysts is solved, and efficient ethylene production and cost-effectiveness are achieved. promote.
Patent Information
- Application Number
- CN202411402864.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The Cu-based catalyst has low Faraday efficiency and low bias current density for carbon dioxide reduction ethylene, and there is a problem of insufficient catalytic activity.
A copper-based catalyst is used to mix and disperse slurry with liquid small molecule alcohols and Nafion solutions as the cathode, and sucrose is added as the additive to form a mixed phase catalyst containing Cu2O and CuO, combining sucrose molecules to regulate the reaction interface to enhance the Catalytic activity and selectivity.
It significantly improves the Faraday efficiency of ethylene to 48.02%, and reduces the cost of catalysts, with industrial application prospects.
Smart Images

Figure HDA0005075744420000011 
Figure HDA0005075744420000021 
Figure HDA0005075744420000022
Abstract
Description
Technical Field
[0001] The present invention belongs to electrolysis CO 2 The technical field of reduction particularly relates to an electrocatalytic reduction system for preparing ethylene by electrochemical reduction of carbon dioxide and its application. Background Art
[0003] CO 2 Conversion into hydrocarbon fuels and chemicals is considered a promising technology strategy in CCUS, and various approaches have been proposed to promote CO 2 Reduction methods include photocatalysis, electrocatalysis, bioconversion and hydrogenation technology. 2 Electrocatalysis has attracted extensive research and discussion due to its unique advantages such as simple system structure, mild reaction conditions, adjustable products and practical applications. In addition, due to the widespread application of intermittent renewable energy, the cost of electricity has decreased, and electrocatalytic CO catalysis driven by green electricity has become a hot topic. 2 The conversion into carbon-based fuels is economically feasible. This strategy can both “eliminate carbon” and store energy, and has unique advantages in achieving the “dual carbon goals”. 2 The multi-carbon (C 2+ ) products include ethylene (C 2 H 4 ), ethane (C 2 H 6 ), ethanol (C 2 H 5 OH), acetic acid (CH 3 COOH), propanol (C 3 H 7 OH), etc. These products are not only of high economic value, but also 1 Products (CO, CH 4 , HCOOH) has a higher energy density and is more conducive to use as an energy substance, which is the target product people expect. Among them, ethylene as an important raw material in the petrochemical industry has attracted the interest of more researchers.
[0004] Copper is the only metal that can 2 During the RR process, considerable amounts of multi-carbon products (C 2+ ) of pure metal, using copper to 2 A series of intermediate substances in the RR process have a unique catalyst feature of special bonding energy. Currently, researchers have improved the electrocatalytic performance of Cu-based catalysts through various strategies such as morphology control, crystal surface exposure, defect engineering, oxidation derivatization, and component regulation. 2 In addition to optimizing the Cu-based catalyst itself, a large number of studies have also reported the effect of electrolyte on CO conversion efficiency.2 The significant effect of RR.
[0005] However, the current Cu-based catalysts have 2+ The overall Faradaic efficiency of the products is not high, especially the Faradaic efficiency of the carbon dioxide reduction product ethylene is low and the partial current density is low. How to improve the catalytic activity of Cu-based catalysts in the carbon dioxide reduction of ethylene is an urgent task. Summary of the invention
[0006] The object of the present invention is to provide an electrocatalytic reduction system for preparing ethylene by electrochemical reduction of carbon dioxide and its application, which has excellent CO 2 Electroreduction to C 2 H 4 catalytic activity and selectivity.
[0007] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0008] Provided is an electrocatalytic reduction system for preparing ethylene by electrochemical reduction of carbon dioxide, comprising: a cathode, an anode and an electrolyte; wherein:
[0009] The cathode is prepared by uniformly dispersing a copper-based catalyst with liquid small molecule alcohols and Nafion solution to obtain a slurry, and then spraying the obtained slurry onto carbon paper;
[0010] The electrolyte is KOH electrolyte containing sucrose additive.
[0011] According to the above scheme, the copper-based catalyst is copper nanoparticles or copper oxide catalyst; wherein the copper oxide catalyst is Cu 2 The mixed phase of O and CuO is composed of uniform nanoparticles with a particle size of 30-50nm connected to each other to form a compact network structure.
[0012] Preferably, the particle size of the copper nanoparticles is 30 nm-50 nm.
[0013] Preferably, the method for preparing the copper oxide catalyst comprises the following steps:
[0014] The copper source solution is added to the reducing agent solution which has been pre-bathed in an ice bath, and the reaction is continued by stirring in the ice bath, and then the solution is allowed to stand for stratification, and the solid product is washed, dried and ground to obtain a copper oxide catalyst.
[0015] More preferably, the copper source is Cu(NO 3 ) 2 、CuSO 4 , CuCl 2 At least one of .
[0016] More preferably, the reducing agent is NaBH4 .
[0017] More preferably, the copper source and NaBH 4 The molar ratio is 1:3-6.
[0018] More preferably, after discarding the supernatant, the mixture is centrifugally washed with deionized water for 3-5 times, and the liquid small molecule alcohol is centrifugally washed for 2-3 times, and then vacuum dried at 40-60° C. overnight. Further preferably, the liquid small molecule alcohol is at least one of ethanol, propanol or isopropanol.
[0019] More preferably, the reaction time under ice bath stirring is 50-80 min.
[0020] According to the above scheme, the copper-based catalyst is mixed with liquid small molecule alcohol and Nafion solution, and then dispersed uniformly by ultrasonication to obtain a slurry. Preferably, the ultrasonication time is 0.5 to 2 hours.
[0021] According to the above scheme, the liquid small molecule alcohol is at least one of ethanol, propanol or isopropanol.
[0022] According to the above scheme, the Nafion solution is an aqueous solution with a Nafion content of 5-10 wt%.
[0023] According to the above scheme, in the slurry, the mass volume ratio of the copper-based catalyst to the solution is: 9-11 mg: 1 mL; the solution is a mixture of liquid small molecule alcohols and Nafion solution, and the volume ratio of the two is 960-980:20-40.
[0024] According to the above scheme, the carbon paper contains hydrophobic PTFE material, wherein the content of F on the surface of the carbon paper is 7-10 wt %.
[0025] According to the above scheme, the concentration of sucrose in the electrolyte is 0.01-0.08 mol / L; preferably 0.01-0.06 mol / L, and more preferably 0.04-0.06 mol / L.
[0026] According to the above scheme, the KOH concentration in the electrolyte is 0.5-2.0 mol / L.
[0027] According to the above scheme, the anode is a catalyst containing metal NiFe prepared on a nickel substrate.
[0028] Provided is an application of the electrocatalytic reduction system for electrochemical reduction of carbon dioxide to produce ethylene, wherein the current density is -100mAcm -2 --400mAcm -2 .
[0029] According to the above scheme, the current density is -300mA cm -2--400mA cm -2 .
[0030] According to the above scheme, the voltage is 0.0V-3.0V.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention provides an electrocatalytic reduction system for preparing ethylene by electrochemical reduction of carbon dioxide, wherein the cathode comprises a copper-based catalyst, and the electrolyte comprises a sucrose additive, and the copper catalytic reaction interface is regulated by sucrose molecules, thereby significantly improving the reaction between reactants and catalytic C near the reaction interface. 2 H 4 The enriched concentration of the generated key intermediates promoted the subsequent CC coupling reaction to generate C 2 H 4 , significantly improving C 2 H 4 Yield.
[0033] 2. This invention is the first to use sucrose molecules as an electrolyte additive for electrocatalytic CO 2 In the reduction reaction, copper-based catalysts have lower costs than precious metal catalysts, sucrose additives are abundant and low-priced, and industrial applications are cost-effective and highly operational, and have prospects for industrial application.
[0034] 3. Further, the copper-based catalyst is selected as a copper oxide catalyst, which is Cu 2 The mixed phase of O and CuO, which is composed of uniform nanoparticles with a particle size of 30-50nm connected to each other to form a tight network structure, combined with the sucrose additive in the electrolyte, is more conducive to the improvement of the Faraday efficiency of ethylene, which can be as high as 48.02%, and has important application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 (a) is a schematic diagram of the process of preparing the copper oxide catalyst obtained in Example 1; (bc) are high-resolution transmission electron microscopy images of the copper oxide catalyst; (d) is an element mapping image of the energy dispersive X-ray spectrum of different elements.
[0036] Figure 2 This is a scanning electron microscope image of the copper oxide prepared in Example 1, wherein a, b, c, and d are at different magnifications.
[0037] Figure 3 Characterization diagram of the copper oxide prepared in Example 1; wherein (a) the X-ray diffraction pattern of the copper oxide catalyst; (b) the X-ray photoelectron spectrum scanning diagram of the catalyst; (c) the fine X-ray photoelectron spectrum diagram of Cu; and (d) the Auger electron spectrum of Cu.
[0038] Figure 4 (a) Element distribution diagram and (b) atomic percentage diagram of the copper oxide catalyst prepared in Example 1 sprayed onto carbon paper; (c) Element distribution diagram and (d) atomic percentage diagram of the original carbon paper used.
[0039] Figure 5 The product Faraday efficiency (FE%) distribution diagram of the copper oxide catalyst prepared in Example 1 in (a) without any additives; (b) 0.025 mol / L citric acid; (c) 0.025 mol / L L-ascorbic acid; (d) 0.025 mol / L sucrose; (e) 0.025 mol / L tannic acid 1M KOH electrolyte; (f) copper oxide catalyst in different additive electrolytes and all at -400 mA cm -2 Ethylene at current density (hereinafter referred to as C 2 H 4 ) FE% comparison chart.
[0040] Figure 6 The copper oxide catalyst prepared in Example 1 was 2 Saturated 1 mol / L KHCO 3 Comparison of (a) linear sweep voltammetry curves and (b) electrochemical impedance spectroscopy of solutions without sucrose and with 0.05 mol / L sucrose added; in situ Raman spectra of the interface of the electrolyte with (c) no sucrose added and (d) with sucrose added.
[0041] Figure 7 The copper oxide catalyst prepared in Example 1 was added to the electrolyte with different sucrose content. 2 H 4 FE% comparison chart, where the sucrose concentrations in ae are 0.00mol / L, 0.01mol / L, 0.025mol / L, 0.05mol / L, and 0.075mol / L, respectively.
[0042] Figure 8 This is a performance test of the electrocatalytic reduction system using commercial copper nanoparticles as catalyst in Example 5. Wherein: Figure (a) shows the electrocatalytic CO reduction reaction with sucrose additive 2 Faraday efficiency distribution diagram of ethylene production. Figure (b) and Figure (c) are FE under different reaction interfaces. C2H4 % contrast and -400mA cm -2 The current density occupied by the preparation of ethylene under C2H4 Refers to) contrast. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] A method for preparing a copper oxide catalyst comprises the following steps:
[0046] (1) Material preparation: Prepare 1 mol / L CuCl 2 The aqueous solution is ready for use. Take 4 ml of 1 mol / L CuCl 2 The aqueous solution and 36 mL of aqueous solution were stirred for 60 min to allow them to be fully mixed, and the solution turned bright green.
[0047] (2) Reduction reaction: Add the mixed solution obtained in step (1) into 20 ml of 1 mol / L NaBH 4 The aqueous solution was stirred in an ice-water bath for 1 hour and allowed to stand to separate the layers.
[0048] (3) Centrifugal washing: Pour off the supernatant of the above mixed solution, perform centrifugal washing four times with deionized water, and then perform centrifugal washing twice with liquid small molecule alcohol. After centrifugation, place in a vacuum drying oven at 60°C and dry overnight, grind the dried powder into fine powder, and the dry powder is the copper oxide catalyst.
[0049] Example 2
[0050] A method for preparing a cathode for electrochemical reduction of carbon dioxide is provided, comprising the following steps:
[0051] Cut 1.5×1.5cm 2 The carbon paper is set aside. Weigh 10 mg of the powdered copper oxide sample prepared in Example 1 and dissolve it in 970 uL of isopropanol solution. At the same time, add 30 uL of 5 wt% Nafion aqueous solution to the solution and ultrasonicate for half an hour until the mixed solution becomes a black uniform slurry. Use a spray gun to evenly spray the slurry onto a 1.5×1.5 cm 2 The cathode for electrochemical reduction of carbon dioxide is obtained by naturally air-drying the carbon paper (F content is 7-10wt%).
[0052] Example 3
[0053] Provided is an electrocatalytic reduction system for electrochemically reducing carbon dioxide, comprising:
[0054] Cathode: cathode prepared in Example 2;
[0055] Anode: A NiFe-containing catalyst prepared by a one-step electrodeposition method on a nickel foam substrate: 0.2 mol / L FeSO 4 (ferrous sulfate) and 0.2 mol / L NiSO 4 (nickel sulfate) solution as the electrolyte, and the 2×3 cm 2 The nickel foam is placed in a three-electrode system for electrodeposition to obtain a catalyst containing metal NiFe.
[0056] Electrolyte: KOH electrolyte containing sucrose additive, wherein the concentration of KOH is 1 mol / L; the concentration of sucrose additive is 0.025 mol / L.
[0057] The cathode, anode, CO 2 The gas cylinder and electrolyte are assembled into a gas reaction cell, through CO 2 The gas cylinder introduces CO into the gas reaction pool. 2 The voltage and current are applied to the reaction cell through the electrochemical workstation, and the reaction product C is collected on the cathode. 2 H 4 .
[0058] Set up control groups with different additives:
[0059] The rest is the same as Example 3, except that the additives in the electrolyte are different, and sucrose is replaced by citric acid, L-ascorbic acid and tannic acid of the same concentration.
[0060] The electrochemical performance of the electrocatalytic reduction system obtained in this example and the control group was compared. Figure 5 .
[0061] Example 4
[0062] Provided is an electrocatalytic reduction system for electrochemically reducing carbon dioxide, comprising:
[0063] Cathode: cathode prepared in Example 2;
[0064] Anode: A catalyst containing metal NiFe prepared by a one-step electrodeposition method on a nickel foam substrate, the specific preparation of which is the same as in Example 3.
[0065] Electrolyte: KOH electrolyte containing sucrose additive, wherein the KOH concentration is 1 mol / L; the concentrations of sucrose additives are 0.01 mol / L, 0.025 mol / L, 0.05 mol / L, and 0.075 mol / L, respectively. At the same time, a control group without sucrose additive was selected.
[0066] The cathode, anode, CO 2The gas cylinder and electrolyte are assembled into a gas reaction cell, through CO 2 The gas cylinder introduces CO into the gas reaction pool. 2 The voltage and current are applied to the reaction cell through the electrochemical workstation, and the reaction product C is collected on the cathode. 2 H 4 .
[0067] The electrochemical performance of the electrocatalytic reduction system obtained in this example and the control group was compared. For specific results, see Figure 7 .
[0068] Example 5
[0069] Provided is an electrocatalytic reduction system for electrochemically reducing carbon dioxide, comprising:
[0070] Cathode: Cut to 1.5×1.5cm 2 Weigh 10 mg of 30nm-50nm commercial Cu nanoparticles and dissolve them in 970uL of isopropanol solution. Add 30uL of 5wt% Nafion aqueous solution to the solution and ultrasonicate for half an hour until the mixed solution becomes a black uniform slurry. Use a spray gun to evenly spray the slurry onto a 1.5×1.5cm 2 on carbon paper (F content is 7-10wt%) and air-dried naturally;
[0071] Anode: A catalyst containing metal NiFe prepared by a one-step electrodeposition method on a nickel foam substrate, the specific preparation of which is the same as in Example 3.
[0072] Electrolyte: KOH electrolyte containing sucrose additive, wherein the KOH concentration is 1 mol / L and the sucrose additive concentration is 0.05 mol / L. Meanwhile, 1 mol / L KOH electrolyte is selected as the control group.
[0073] The cathode, anode, CO 2 The gas cylinder and electrolyte are assembled into a gas reaction cell, through CO 2 The gas cylinder introduces CO into the gas reaction pool. 2 The voltage and current are applied to the reaction cell through the electrochemical workstation, and the reaction product C is collected on the cathode. 2 H 4 .
[0074] The electrochemical performance of the electrocatalytic reduction system obtained in this example and the control group was compared. For specific results, see Figure 8 .
[0075] Test Example 1
[0076] This test is used to illustrate the microscopic morphology of the copper oxide catalyst material of the present invention.
[0077] Figure 1 A schematic diagram of the process for preparing a copper oxide catalyst in Example 1 and a morphology diagram of copper oxide are shown. Figure 1 (a) shows the preparation process of copper oxide catalyst, which is to use NaBH in an ice-water bath environment. 4 It is prepared by a one-step reduction method. Figure 1 As shown in (b), the surface morphology of the catalyst was tested by using TEM (transmission electron microscopy). It can be seen that the copper oxide catalyst is composed of uniform nanoparticles with a diameter of about 30 to 50 nm connected to each other to form a tight network structure. The nanoscale catalyst morphology can increase the exposure of active sites and can be used in the electrocatalytic CO 2 In the reduction reaction with CO 2 The gas has better contact. The microstructure can be further revealed by high-resolution TEM, where Cu 2 The lattice fringes of O and CuO are relatively clear, and the lattice spacing is It belongs to the CuO(111) crystal plane. The lattice spacing is Attributed to Cu 2 O(111) crystal plane, such as Figure 1 (c) Cu 2+ The presence of may be due to reoxidation by oxygen during the preparation process. From the element mapping diagram, it can be seen that the main distributed elements are Cu and O and they are evenly distributed. Figure 2 This is a scanning electron microscope image of the copper oxide of Example 1. It can be seen that the prepared copper oxide is dense nanoparticles, and the nanoparticles are stacked to form a series of nanoparticle clusters.
[0078] Test Example 2
[0079] This test is used to illustrate the physical structure of the copper oxide catalyst material of the present invention.
[0080] Figure 3 The phase structure diagram of the copper oxide catalyst prepared in Example 1 is shown to facilitate us to determine the chemical valence state of the synthesized copper oxide. Figure 3 (a), compared with standard cards CuO (PDF#48-1548) and Cu 2 O (PDF#06-0667) showed that the copper oxide catalyst showed diffraction peaks of CuO (1 1-1), (1 11), (2 0-2) and (1 1-3) crystal planes at 2θ = 35.5°, 38.7°, 48.7° and 61.5°, and Cu at 2θ = 36.4°, 42.3°, 48.7°, 73.5°. 2 The diffraction peaks of O(11 1), (2 0 0) and (3 1 1) crystal planes indicate that CuCl 2After sodium borohydride reduction, Cu 2+ With Cu + The CuO and Cu 2 O mixed phase (copper oxide). In order to further analyze the elemental composition and chemical valence state of the surface, we also performed X-ray photoelectron spectroscopy tests on the copper oxide catalyst. The test results are as follows: Figure 3 (bc). Figure 3 (b) is the full spectrum test diagram of the copper oxide catalyst, where the positions of Cu 2p, O 1s, C 1s and Cu Auger spectra in the full spectrum can be seen. Figure 3 (c) The fine spectrum of Cu 2p after reaction is divided into Cu 2p 2 / 3 and Cu 2p 1 / 3 The results show that since the +2 copper will spontaneously change its valence state to 0 and +1 during the reaction, the copper oxide catalyst is mainly Cu + / Cu 0 There is a small amount of Cu 2+ state, Figure 3 (d) is the Auger spectrum of Cu, where the 570.3 eV position is attributed to Cu + characteristic peaks.
[0081] Test Example 3
[0082] This test is used to illustrate the microscopic morphology of the copper oxide catalyst material in Example 2 of the present invention sprayed onto commercial carbon paper.
[0083] like Figure 4 (a) It can be seen that the copper oxide catalyst still exists in the form of nanoparticles and is distributed more evenly. From the element mapping images of the energy dispersive X-ray spectrum of different elements, it can be seen that the three elements Cu, O, and F are evenly distributed, as shown in Figure 2. Figure 4 As shown in (b), the atomic percentage of F element is 9.82%. To verify the source of F element, we also conducted a scanning electron microscope test on the carbon paper used to prepare the gas diffusion electrode. Figure 4 As shown in (c), it can be seen that the surface of the carbon paper is flat and uniform. Figure 4 (d) It can be seen that there are a large amount of C elements and a small amount of F elements in carbon paper. Commercial carbon-based GDL consists of densely packed mesoporous carbon layers (carbon paper or carbon cloth) and densely packed microporous layers (hereinafter referred to as MPL) (carbon nanofibers or compressed carbon powder). In order to optimize commercial carbon-based GDL, inert F-containing hydrophobic substances are generally mixed in MPL, so F elements are present.
[0084] Test Example 4
[0085] This test is used to illustrate the effect of adding different types of additives on CO 2 Electroreduction to C 2 H 4 Performance impact.
[0086] Figure 5 The performance of the copper oxide catalyst prepared in Example 1 in the electrolyte solution with different additives for electrocatalytic CO2RR is shown in -100 mA cm -2 、-200mA cm -2 、-300mAcm -2 、-400mA cm -2 and -500mA cm -2 The test was carried out under the current density. Figure 5 As shown in (a), without any additive, the current density increases with the increase of C 2 H 4 The Faraday efficiency shows a trend of gradual increase. -2 The Faraday efficiency for ethylene at a current density of only 23.26% is low. The total Faraday efficiency (FE) does not reach 100% at low current density. The possible reason is that the flow rate of the gas product entering the gas chromatograph (hereinafter referred to as GC) is lower than the flow rate of the inlet CO 2 At a higher current density, C 2 H 4 The increase in Faraday efficiency is not obvious. After adding 0.025mmol citric acid to 1mol / L KOH electrolyte solution, Figure 5 As shown in (b), at high current density, C 2 H 4 The Faraday efficiency has been significantly improved at -400mA cm -2 Lower C 2 H 4 The Faradaic efficiency reaches 34.63% and with the increase of current density, C 2 H 4 The Faraday efficiency is still increasing gradually. Figure 5 (c) and 5(e) show that the electrolyte with 0.025mmol / L L-ascorbic acid and 0.025mmol / L tannic acid added has a better effect on the electrocatalytic CO 2 The selectivity of reduction to ethylene was not improved. Figure 5 As shown in (d), when 0.025 mmol / L sucrose is added to the electrolyte solution, it can be clearly observed that at each current density, C 2 H 4 The Faraday efficiency has been significantly improved at -400mA cm-2 The current density reached 42.37%. In summary, Figure 5 As shown in (f), the copper oxide catalyst is at -400 mA cm -2 C in electrolytes with different additives 2 H 4 By comparison, it can be seen that the use of sucrose additive can significantly promote the electrocatalytic CO 2 Performance of reduction to produce ethylene.
[0087] Test Example 5
[0088] This test is used to illustrate the effect of adding different amounts of sucrose additives on CO 2 Electroreduction to C 2 H 4 Performance impact.
[0089] The performance analysis was carried out using a gas diffusion electrode flow cell (hereinafter referred to as GDE-cell), a gas chromatograph and a H-NMR 400 nuclear magnetic resonance spectrometer. Figure 6 This is a comparison of the electrocatalytic reduction system without additives and with 0.05 mol / L sucrose additive. Figure 6 (a) It can be seen that the presence of additives has little effect on the current density in the electrochemical reduction system. Considering the same cathode material used, it is likely to have the same electrochemically active surface area and the same intrinsic electrochemical activity. Electrochemical impedance spectroscopy (EIS) was then performed to understand the effect of sucrose additives on electron transfer in the electrolyte. It can be seen that the electrochemical impedance in the electrochemical system containing 0.05 mol / L sucrose additive is significantly smaller than that in the electrochemical system without additives, with the smallest charge transfer resistance, and in the electrocatalytic CO 2 Reduction is more conducive to charge transport, such as Figure 6 (b) as shown.
[0090] To further understand the electrocatalytic CO 2 Information on key reaction intermediates adsorbed on the catalyst surface during the reduction process and C 2+ To investigate the reaction pathway of the products, we conducted in situ Raman spectroscopy tests at different potentials. Figure 6 As shown in (c, d), at open circuit potential, the -1 The Raman characteristic peak attributed to CuO was observed at the position. When a negative potential was applied, the Raman characteristic peak of CuO disappeared, indicating that the electrocatalytic CO 2 During the reduction process, the metal copper was reduced, which is consistent with the XRD spectrum measured after the reaction. At the same time, several obvious Raman peaks were observed in the chemical reduction system with and without sucrose additives in the electrolyte. Among them, 1040-1100cm-1 1340-1400cm -1 、1600cm -1 The corresponding ones are carbonate ions, bicarbonate ions and water. In addition, when the applied potential is -0.1 (V vs. RHE), the -1 The characteristic peak of the stretching vibration of the *CO intermediate was found nearby, and the characteristic peak signal intensity lasted until -0.5 (V vs. RHE). When the applied voltage was more negative, the *CO signal intensity rapidly weakened until it disappeared. The *CO intermediate is the *CO-*CO coupling to form C 2+ Key intermediates of the product, comparison Figure 6 (c) and (d) show that the characteristic peak signal of the *CO intermediate is stronger after adding sucrose additive to the electrolyte, indicating that the *CO coverage on the Cu surface is higher, which is more beneficial to the subsequent CC coupling to produce ethylene. After applying a potential lower than -0.5 (V vs. RHE), the intensity of the *CO characteristic peak signal decreases, indicating that the CO intermediate desorbs from the Cu surface and participates in the subsequent CC coupling reaction.
[0091] Depend on Figure 7 It can be seen that the concentration of sucrose additives will affect the electrocatalytic CO 2 The reduction reaction performance was affected by the addition of sucrose, and the sucrose concentration gradients of no sucrose, 0.01mmol / L, 0.025mmol / L, 0.05mmol / L and 0.075mmol / L were selected for electrocatalytic CO 2 RR test, respectively at -100mA cm -2 、-200mA cm -2 、-300mA cm -2 、-400mA cm -2 and -500mA cm -2 The test was carried out under current density. Figure 7 a It can be seen that without any additives, as the current density increases, C 2 H 4 The Faraday efficiency shows a trend of gradual increase. -2 The Faraday efficiency of ethylene at a current density of only 23.26% is low, and the yield of ethylene at a high current density is Figure 7 (be) It can be seen that the addition of a certain amount of sucrose additive has an important effect on the electrocatalytic performance of copper oxide catalysts for CO 2 The selectivity of ethylene reduction has a certain promoting effect. With the increase of sucrose concentration, the Faraday efficiency of ethylene also increases. When the concentration of sucrose is 0.05mmol / L, at -400mAcm -2The Faraday efficiency of ethylene can reach 48.02% at a current density of 1.34 W. With the further increase of sucrose concentration, the Faraday efficiency of ethylene decreased to 35.08%. This may be because excessive sucrose molecules will destroy the hydrogen bond network in the double electrical layer and reduce the basis of protons and active sites. However, too thin proton concentration will significantly weaken the CO 2 The reduction hydrogenation process required in RR. This inference can be obtained from Figure 7 As can be seen in (e), the excess sucrose molecules not only reduce the selectivity of ethylene, but also increase the selectivity of CO as a result of weakening the reductive hydrogenation process. Figure 7 (f) It can be seen intuitively that the ethylene selectivity is most significantly improved when the concentration of sucrose additive is 0.05 mmol / L.
[0092] Test Example 6
[0093] This test is used to illustrate the performance test of the electrocatalytic reduction system obtained by using commercial Cu nanoparticles in Example 5 in the present invention.
[0094] The performance of Example 5 was analyzed using a gas chromatograph and a H-NMR 400 nuclear magnetic resonance spectrometer.
[0095] like Figure 8 (ac), original commercial copper nanoparticles at -400 mA cm -2 The Faradaic efficiency of ethylene is 37.29% at a current density of -400 mA cm -2 The Faradaic efficiency of ethylene can reach 40.96% at a current density of .
[0096] In summary, this will provide a basis for the future study of the effects of additives on electrocatalytic CO 2 The reduction reaction provides new ideas.
[0097] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
Claims
1. An electrocatalytic reduction system for preparing ethylene by electrochemical reduction of carbon dioxide, characterized in that: It comprises a cathode, an anode and an electrolyte; wherein: The cathode is prepared by uniformly dispersing a copper-based catalyst with liquid small molecule alcohols and Nafion solution to obtain a slurry, and then spraying the obtained slurry onto carbon paper; The electrolyte is KOH electrolyte containing sucrose additive.
2. The electrocatalytic reduction system according to claim 1, characterized in that: The copper-based catalyst is copper nanoparticles or copper oxide catalysts; wherein the copper oxide catalyst is a mixed phase of Cu2O and CuO, and is composed of uniform nanoparticles with a particle size of 30-50nm interconnected to form a tight network structure.
3. The electrocatalytic reduction system according to claim 2, characterized in that: The method for preparing the copper oxide catalyst comprises the following steps: The copper source solution is added to the reducing agent solution which has been pre-bathed in an ice bath, and the reaction is continued by stirring in the ice bath, and then the solution is allowed to stand for stratification, and the solid product is washed, dried and ground to obtain a copper oxide catalyst.
4. The electrocatalytic reduction system according to claim 3, characterized in that: The copper source is at least one of Cu(NO3)2, CuSO4, and CuCl2; and the reducing agent is NaBH4.
5. The electrocatalytic reduction system according to claim 3, characterized in that: The molar ratio of copper source to NaBH4 is 1:3-6; the reaction time is 50-80 min with stirring in an ice bath.
6. The electrocatalytic reduction system according to claim 1, characterized in that: The liquid small molecule alcohol is at least one of ethanol, propanol or isopropanol; the Nafion solution is an aqueous solution with a Nafion content of 5-10 wt%.
7. The electrocatalytic reduction system according to claim 1, characterized in that: In the slurry, the mass volume ratio of the copper-based catalyst to the solution is: 9-11 mg: 1 mL; the solution is a mixture of liquid small molecule alcohols and Nafion solution, and the volume ratio of the two is 960-980:20-40.
8. The electrocatalytic reduction system according to claim 1, characterized in that: The carbon paper contains hydrophobic PTFE material, wherein the content of F on the surface of the carbon paper is 7-10wt%.
9. The electrocatalytic reduction system according to claim 1, characterized in that: In the electrolyte, the sucrose concentration is 0.01-0.08 mol / L; the KOH concentration is 0.5-2.0 mol / L.
10. Use of the electrocatalytic reduction system according to any one of claims 1 to 9, characterized in that: Used for electrochemical reduction of carbon dioxide to produce ethylene, where the current density is -100mAcm -2 --400mAcm -2 .
Citation Information
Cited By
Preparation method and application of CuO / hollow structure CeO2 electrocatalyst
CN119932627A
A method for preparing CuO / hollow structure CeO2 electrocatalyst and its application
CN119932627B
Preparation method and application of CuO / MgO nano-catalyst
CN119932628A
Preparation method and application of CuO / MgO nano catalyst
CN119932628B
Synthetic method for in-situ construction of Cu < + > / Cu0 interface nano-catalyst based on heteroatom induction
CN120250063A